The 30th Anniversary of the Applied linguistics department of Lesya Ukrainka Volyn National University - Biskub, Iryna; Rohach, Oksana; Sherik, Daniel (Lesya Ukrainka Volyn National University, 2023)
The article is devoted to the creation and development of the department of applied linguistics at the Lesya Ukrainka Volyn national university, its achievements, evolution, cooperation with other educational programs at the Ukrainian and foreign educational institutions.
Стаття-огляд присвячена 30-й річниці створення кафедри та спеціальності Прикладна лінгвістика у Волинському національному університеті імені Лесі Українки, особливостям освітньої програми, викладачам кафедри, які забезпечували підготовку фахівців у галузі прикладної лінгвістики.
Keywords: applied linguistics; history; evolution; achievements; Lesya Ukrainka Volyn National University; 37.091.33